Portrety nadawców w wybranych tekstach prasy postlandsberskiej. Szkic klasyfikacyjny = Portraits of Broadcasters in Selected Postlandsberg Press Texts Classification Draft - Taborska, Katarzyna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
As a result of post-Yalta agreements Polish borders were moved to the west after World War II. Thus, a new German-Polish border was formed. This includes the Landsberg-Gorzów borderline, which appeared at the time of transforming German (since its founding in 1257 until 1945) Landsberg on the Warta river into the Polish-language Gorzów during the second half of the forties of the twentieth century. The city`s transubstantiation stage was named the Postlansberg period, in an effort to capture the moment of disappearance of German - language traditions and the hatching of new cultural signals. Literature which appeared during this period and which is associated with this place is defined as Postlandsburg literature. It includes a variety of texts written in Polish and German. This article presents representative images of broadcasters present in the first periodicals issued in Landsberg on the Warta River, taken over by the Poles in March 1945: "Ziemia Gorzowska" and "Ziemia Lubuska". Thse writings were weeklies, but de facto acted as daily newspapers. Among the portraits of broadcasters these are distinguished: German printers, Polish settlers in the new borderland, proponents of the new government, informants / rapporteurs, teachers of readers, co-creators of the myth of "recovered land". These broadcaster portraits in certain texts were connected, gaining a hybrid character. The classification of these portraits can facilitate the analysis of one of the most important post-war myths of the PRL (People`s Poland) - the myth of "reclaimed land" and a deeper knowledge of the mechanisms of media images of the new borderlands.
Keywords: nadawca; prasa; Gorzów Wielkopolski; II wojna światowa; Ziemia Gorzowska (czasopismo); Ziemia Lubuska (czasopismo); broadcaster; press; Landsberg a/ Warthe; world war II